Práticas pedagógicas de leitura e escrita : um estudo investigativo no ciclo da alfabetização - Ebert, Síntia Lúcia Faé (2016)
This Doctoral Dissertation in Education is part of the research line Training, Policies and Practices in Education, of the Graduate Program in Education of the Pontifical Catholic University of Rio Grande do Sul (PPGEdu / PUCRS), and presents a study that investigated the pedagogical practices for the teaching of reading and writing developed in the literacy cycle, i.e. the first three years of elementary education in a public school that showed favorable results in a National Assessment that evaluates the level of learning and school flow of students - the IDEB. The research was conducted in a public school of the State Network that obtained, among public schools belonging to the municipality of Porto Alegre, a favorable assessment in the IDEB released in 2013. The choice of this school for the research was for its good reading and writing practices developed in the literacy cycle. The theoretical framework that guided the study was based primarily on authors such as Carvalho (2004), Fernandes (2008), Ferreiro (1993, 2001, 2012), Ferreiro and Teberosky (1999), Freire (2005, 2011), Morais (2012), Mortatti (2000), Russo (2012), Soares (2006, 2008) and Solé (1998). Methodologically, a qualitative research was done; a case study was developed in the perspective of Lüdke and André (2013). The participants were three (3) female teachers, of three (3) classes, 1st, 2nd, and 3rd years of elementary school and the students of these teachers. The research instruments used for data collection were participant observation, developed over thirty-eight (38) lessons, distributed in the three groups investigated and recorded in the class diary; semi-structured interviews applied to three teachers who participated in the research, and documentary analysis of the Study Plans intended for the three groups. Data analysis was developed from the content analysis (BARDIN, 2011), and three categories of analysis were identified: a) reading and writing in the literacy cycle: from teaching the first letters to fluent text writing and reading; b) playfulness in the literacy cycle; c) learning beyond the school curriculum; being each category divided into subcategories. Through these analyses, based on the theoretical framework that supports this dissertation, on the research materials, and on the researcher’s inferences, it is clear that there is, in the investigated school, a well-structured literacy cycle regarding pedagogical practices of reading and writing; a favorable environment for the development of the lessons, as well as support of the school management in pedagogical processes. Another conclusion is that for the carrying out of significant pedagogical practices of reading and writing, it is important to have a pedagogical work that aims to favor the child’s completion of the first year being able to read and having an alphabetic writing. In the following years that complete the literacy cycle, the work that involves reading, writing and text production in a playful manner and with quality is expected to continue.